PENGEMBANGAN MEDIA BIG BOOK PADA TEMA PERTUMBUHAN DAN PERKEMBANGAN MAKHLUK HIDUP SUBTEMA 1 UNTUK SISWA KELAS III SEKOLAH DASAR - Nur Three Harzuliana; Neni Hermita; Jesi Alexander Alim (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2022)
This study aims to develop a big book learning media on the theme of growth and development of living things sub-theme 1 which is valid and practical for third grade elementary school students. This research is research and development, and the researcher applies the ADDIE model which consists of 5 stages: analysis, design, development, implementation, and evaluation. The learning media developed was validated by 2 media experts. To test the practicality, the researcher distributed questionnaires to teachers and students. The data in this study were obtained through interviews, questionnaires, and student learning outcomes in the form of LKPD. The data obtained were then analyzed quantitatively and descriptively. The learning media developed was very valid with an average score of 87.03% and included in the very practical category with an average score of 93.05% from teachers and 90.55% from students. Student learning outcomes in the form of LKPD with an average score of 83.33%. Therefore, the big book learning media with the theme of growth and development of living things in sub-theme 1 can be used by elementary school students and teachers.